(untitled) (Revista Española de Derecho Internacional, 2006)
International obligations must be complied with according to international law. However, the necessary measures of enforcement of those obligations are not usually determined by general international law itself, nor are the ways in which these compromises should be incorporated into national legal orders –an issue closely related to, but different from, the compliance with international obligations-. The present article studies these general issues on compliance applied to the WTO Dispute Settlement System. In particular, the article analyses both the measures to create incentives for the compliance with the decisions of the Dispute Settlement Body and the specific measures of execution of those decisions and their incorporation into domestic legal orders, using the example of the practice developed by the European Community. In order to achieve these goals, the author presents her views on the normative character, efficacy and autonomy of the WTO Dispute Settlement System and also on the binding character of the decisions of Dispute Settlement Body.